Nutritional counseling in athletes: a systematic review - Fiorini, Simona; Neri, Lenycia De Cassya Lopes; Guglielmetti, Monica; Pedrolini, Elisa; Tagliabue, Anna; Quatromoni, Paula A.; Ferraris, Cinzia (Frontiers in Nutrition, 2023)
Many studies report poor adherence to sports nutrition guidelines, but there is a lack of research on the effectiveness of nutrition education and behavior change interventions in athletes. Some studies among athletes demonstrate that nutrition education (NE), often wrongly confused with nutritional counseling (NC), alone is insufficient to result in behavior change. For this reason, a clear distinction between NC and NE is of paramount importance, both in terms of definition and application. NE is considered a formal process to improve a client's knowledge about food and physical activity. NC is a supportive process delivered by a qualified professional who guides the client(s) to set priorities, establish goals, and create individualized action plans to facilitate behavior change. NC and NE can be delivered both to individuals and groups. To our knowledge, the efficacy of NC provided to athletes has not been comprehensively reviewed. The aim of this study was to investigate the current evidence on the use and efficacy of NC in athletes. A systematic literature review was performed based on the PRISMA method. The search was carried out in PubMed, Scopus, Web of Science, Science Direct, Cochrane Library. Inclusion criteria: recreational and elite athletes; all ages; all genders; NC strategies. The risk of bias was assessed using the RoB 2.0 Cochrane tool. The quality of evidence checking was tested with the Mixed Methods Appraisal Tool system. 10 studies were included in this review, with athletes representing different levels of competition and type of sports. The most commonly applied behavior change theory was Cognitive Behavioral Theory. NC was delivered mainly by nutrition experts. The intervention duration ranged from 3 weeks to 5 years. Regarding the quality of the studies, the majority of articles reached more than 3 stars and lack of adequate randomization was the domain contributing to high risk of bias. NC interventions induced positive changes in nutrition knowledge and dietary intake consequently supporting individual performance. There is evidence of a positive behavioral impact when applying NC to athletes. Additional studies of sufficient rigor (i.e. randomized controlled trials) are needed to demonstrate the benefits of NC in athletes.